Intergenerational mobility of immigrants in Germany: moving with natives or stuck in their neighborhoods? - Mutlu Yuksel (Institute for the Study of Labor (IZA), 2009)
In this paper, I analyze intergenerational mobility of immigrants and natives in Germany. Using the German Socioeconomic Panel (GSOEP), I find intergenerational elasticities that range from 0.19 to 0.26 for natives and from 0.37 to 0.40 for immigrants. These elasticity estimates are lower than typically found for the U.S. and imply higher mobility in Germany than in the U.S. However, as in the U.S., I find greater mobility among German natives than among immigrants. Moreover, I investigate to what extent the lower mobility among immigrants in Germany is due to ethnic capital as suggested by Borjas (1992). I find that the impact of father's earnings on son's earnings remains virtually unchanged when including a measure of ethnic capital, suggesting that the higher father-son correlation found among immigrants is not due to omitting ethnic capital. However, I do find a large independent effect of ethnic capital on sons' earnings (the coefficient is 0.81 as opposed to 0.25 found by Borjas (1992)). These results are consistent with estimates from Microcensus data, where the combined effect of parents' and ethnic capital is close to unity. Thus, contrary to the U.S. results which suggest convergence of immigrants' earnings towards natives' earnings, the German results suggest divergence of immigrant earnings.
Keywords: J61; J62; 330; Immigration; intergenerational mobility; natives; ethnic capital; Migranten; Soziale Mobilität; Intergenerational Mobility; Generationenbeziehungen; Ethnische Gruppe; Social Capital; Schätzung; Deutschland